Chapter 19 Quantification Theoretical perspectives - Kimmelman, Vadim (Taylor & Francis, 2021)
The study of quantificational expressions is one of the central domains in the field of natural language semantics. Probably every language has means of expressing quantification, but quantifiers in natural languages are straightforwardly parallel to logical quantifiers. Based on the previous research on quantification in sign languages, we further discuss the following issues: lexical quantifiers, quantificational morphology, and structural aspects of quantification. The idea behind A-quantification stems from the analysis of indefinites by Kamp and Heim, according to which indefinite expressions are non-quantificational, and they just introduce a variable with descriptive content that must be unselectively bound by a quantifier. In opposition to D-quantification, Bach et al. group other ways of encoding quantification under the label A-quantification, which includes adverbs, auxiliaries, affixes, and argument-structure adjusters. A large variety of verbal modifiers that express different types of distributive semantics has been found in RSL by Filimonova.